The Impact of Entrepreneurship Education and Motivation on Entrepreneurial Intentions: Creativity as a Mediating Factor - Satria Lintang Rachmadana; Salim Diarra (Universitas Negeri Makassar, 2024)
This study explores the impact of entrepreneurship education and motivation on students' entrepreneurial intentions, with creativity serving as a mediating factor. The research adopts a quantitative approach, focusing on how these elements influence entrepreneurial interest among students in an entrepreneurship study program. The findings indicate that both entrepreneurship education and motivation have a direct and significant impact on students' entrepreneurial intentions. However, the study also reveals that while entrepreneurship education and motivation are crucial, their effect on creativity does not show a significant direct influence. Nonetheless, creativity does play an important indirect role, mediating the relationship between entrepreneurship education, motivation, and entrepreneurial interest. These insights can be valuable for educators and lecturers, highlighting the need to guide and inspire students not only in gaining knowledge but also in fostering a genuine interest in business management. This approach ensures that students are equipped with the necessary skills and motivation to pursue and develop their own business ventures, thereby enhancing their entrepreneurial potential.